Effect of the morphology measuring methods of coconut fiber on the determination of mechanical tensile properties (2022)
This study is intended to improve the methodology to calculate the tensile properties of natural coconut fiber and increasing confidence in the use of sustainable natural fibers as reinforcing in composites used for different components in the naval industry. Coconut fiber is an agribusiness by-product that has been shown to have the potential for the development of new materials. The morphology of different species of coconut fiber was studied, and their mechanical tensile properties were determined. The coconut fibers were tested under direct tension in a universal testing machine, and the cross-sectional area of the fibers was calculated using images obtained in an optical microscope and a scanning electron microscope. The study assessed the incidence of key factors to determine coconut fiber mechanical tensile properties including different area measuring methods and the percentage of lumens present through an image analysis software called ImageJ. The results indicate that coconut fiber has a round-shaped cross-section, and the percentage of lumens is between 15% and 27%. Therefore, the effective area is reduced increasing the fiber’s ultimate resistance to tension.